Design of Wearable Patient Lying Position Tracking and Warning System to Prevent Pressure Injury - Koşun, Ali Erdem; Atçı, Mehmet Yakup; Tatar, Ahmet Burak; Tanyıldızı, Alper K.; Taşar, Beyda (My University, 2022)
Within the scope of this study, a wearable lying position tracking system equipped with inertial measurement unit sensors has been developed to prevent the formation of pressure injuries in bedridden patients. Three inertial measurement unit sensors were placed on the patient's chest, one on the right upper leg and the other on the left upper leg, and the angular orientation expressions of the limbs were calculated. Datasets were created for three different lying positions, and machine learning models were used to classify the patient's lying position. The success of the classifiers was compared by calculating the accuracy, sensitivity, specificity, precision and F1 score values. The average accuracy values in the lying position classification were obtained as 99.506%, 99.977%, 99.972%, 99.838%, and 99.967% respectively, using linear discriminant analysis, k-nearest neighbor, decision tree, support vector machine and random forest classification methods. The highest accuracy rate was obtained as a result of the k-nearest neighbor method with high variation. The time that the person remained fixed in the determined lying position was also calculated, and if it remained longer than the specified time, an audible warning signal was generated to change the position. Thus, it has been tried to prevent the person to apply pressure by lying on a single muscle group and tissue for a long time and to prevent the formation of pressure injuries over time
Keywords: Mikroskopi; Mühendislik; Biyotıp; Tıbbi İnformatik; Bilgisayar Bilimleri; Yazılım Mühendisliği; Genel ve Dahili Tıp; Sağlık Bilimleri ve Hizmetleri